Not a song like any other : an anthology of writings by Mori Ogai - Rimer, J. Thomas; Mori, Ōgai, 1862-1922 (University of Hawaii Press, 2004)
The literary writings of Mori Ōgai (1862-1922), one of the giant figures of the Meiji period, have become increasingly well known to readers of English through a number of recent translations of his novels and short stories. Ōgai was more than a writer of fiction, however. He has long been regarded in Japan as one of the most influential intellectual and artistic figures of his period, possessing a wide range of enthusiasms and concerns, many developed through his early European experiences. Not a Song Like Any Other attempts to reveal the full range of Ōgai's creative endeavor, providing trenchant examples of his remarkable range, from dramatist and storyteller to poet and polemicist, all translated into English for the first time. The first of seven parts, "The Author Himself," offers a variety of self portraits and other insights into Ōgai's character through his essays--laconic, ironic, detached--written over the course of his career. "Mori Ōgai in Germany" reveals his responses to living in Germany in the 1880s and seeing for the first time how his country was being interpreted from the outside. It includes his celebrated and spirited defense of his country, originally published in a German newspaper. "Mori Ōgai and the World of Politics" relates his uneasy reactions to Japanese society at a later phase in his career. The fourth section provides some of the first information available in English concerning his lifelong interest in painting and other aspects of the visual arts in the Japan of his day. Ōgai's theatrical experiments are briefly chronicled in Part 5. "Four Unusual Stories" offers new evidence of the range of the writer's interests and ambitions. The final section includes some of the first translations of Ōgai's poetry available in English. Contributors: Richard Bowring, Sarah Cox, Sanford Goldstein, Andrew Hall, Mikiko Hirayama, Helen Hopper, Marvin Marcus, Keiko McDonald, J. Thomas Rimer, Hiroaki Sato, William J. Tyler